PELAYANAN KESEHATAN DARI KAJIAN HUKUM DAN HAK ASASI MANUSIA - Adam, Nilawati; Liwa, Maria Ana (STIH Awang Long Samarinda, 2018)
Health services can be obtained from the level of the community health centers (Puskesmas), hospitals, private practice doctors and others. Today's society is increasingly critical of health services and health professionals. The community demands good health care from the hospital, on the other hand the government has not been able to provide services as expected because of limitations, except for private hospitals that are business oriented, can provide good health care. Health workers are expected to be able to have 5 roles, namely Care providers, Decision-makers, Communicators, Community Leaders, and Managers who have adequate management capacity in providing quality health services.